Offshoring and wages: Evidence from EU manufacturing industries - Hamulczuk, Mariusz; Kraciuk, Jakub (Wpływ offshoringu na płace w przemyśle przetwórczym krajów UE, 2019)
Progressing globalization processes are evidenced in e.g. the relocation of production and service processes abroad, a practice referred to as offshoring. They might result in changes in local labour markets all over the world. In this context, the purpose of this study was to evaluate the impact of offshoring on the level of wages in the manufacturing industries of European Union member countries. The research was based on data from 19 industries from the WIOD database (edition 2016). In order to examine the influence of offshoring on wages, panel models with fixed effects were applied. A generalized least squares method was used for their estimation. The results obtained indicate that offshoring might have a negative impact on wages in the “old EU” member countries and a neutral influence on wages in the “new EU” countries. At the same time, it was noticed that the impact of offshoring on wages might differ significantly between industries
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 47-57
Keywords: offshoring; labour market; wages; rynek pracy; płace